Automated measurements of gas‐liquid mass transfer in micropacked bed reactors. Issue 2 (5th September 2017) - Zhang, Jisong; Teixeira, Andrew R.; Jensen, Klavs F.
Abstract : Gas‐liquid mass transfer in micropacked bed reactors is characterized with an automated platform integrated with in‐line Fourier transform infrared spectroscopy. This setup enables screening of a multidimensional parameter space underlying absorption with chemical reaction. Volumetric gas‐liquid mass‐transfer coefficients (k L a) are determined for the model reaction of CO2 absorption in a methyl diethanolamine/water solution. Parametric studies are conducted varying gas and liquid superficial velocities, packed bed dimensions and packing particle sizes. The results show that k L a values are in the range of 0.12∼0.39 s −1, which is about one‐to‐two orders of magnitude larger than those of conventional trickle beds. An empirical correlation predicts k L a in micropacked bed reactors in good agreement with experimental data . © 2017 American Institute of Chemical Engineers AIChE J, 64: 564–570, 2018